Influence of Leadership Orientation and Level of Awards Against Employee Loyalty in Lancang Kuning University - Tanjung, Abrar; Giatman, Giatman; Ambiyar, Ambiyar; Syahril, Syahril (International Journal for Educational and Vocational Studies, 2020)
Human resources are people who design and produce goods or services, oversee quality, market products, allocate financial resources and formulate all strategies and objectives of the organization. Full and continuous management and utilization of existing human resources so that they can work optimally, effectively and productively in achieving organizational or company goals. Lancang Kuning University is an educational institution that has administrative and teaching and learning activities. The total number of employees or employees is 513, consisting of 377 educators and 144 education staff. Simultaneous Influence. Based on the results of the discussion, the simultaneous influence of leadership orientation and rewards on employee loyalty is 32.1%, while the remaining 67.9%, while the partial effect of multiple regression analysis shows that supervision has an influence on employee work discipline by 0.435, awards have an influence to employee loyalty of 0.279.